2013
DOI: 10.4236/as.2013.46039
|View full text |Cite
|
Sign up to set email alerts
|

Influence of late emerging weeds in glyphosate-resistant corn

Abstract: Fifteen field trials were conducted from 2009 to 2011 in Ontario, Canada and Michigan, USA to determine how long glyphosate-resistant corn needs to be kept weed-free after emergence to prevent yield loss. Data were separated into two environments based on when yield loss first occurred after glyphosate application. In Environment 1 (4/15 sites) yield was not reduced when corn was kept weed-free until the 4-leaf stage. However, in Environment 2 (11/15 sites) there was no yield loss when corn was kept weed-free … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 19 publications
0
6
1
Order By: Relevance
“…Season-long control of velvetleaf, a mixture of smooth and redroot pigweed referred to hereafter as pigweed species, common ragweed, common lambsquarters, and large crabgrass was estimated by collecting weed population density and above-ground weed biomass data 8 WAT. Research has shown that weeds emerging after the fourleaf stage of corn do not influence yields; furthermore, weeds emerging after the six-leaf stage are not likely to reach reproductive maturity (Soltani et al 2013). Weed population density and above-ground biomass data were obtained by counting the weeds present in two half-meter quadrats and then the weeds were cut at the soil surface, dried, and weighed.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Season-long control of velvetleaf, a mixture of smooth and redroot pigweed referred to hereafter as pigweed species, common ragweed, common lambsquarters, and large crabgrass was estimated by collecting weed population density and above-ground weed biomass data 8 WAT. Research has shown that weeds emerging after the fourleaf stage of corn do not influence yields; furthermore, weeds emerging after the six-leaf stage are not likely to reach reproductive maturity (Soltani et al 2013). Weed population density and above-ground biomass data were obtained by counting the weeds present in two half-meter quadrats and then the weeds were cut at the soil surface, dried, and weighed.…”
Section: Methodsmentioning
confidence: 99%
“…For pigweed species, common ragweed, common lambsquarters and large crabgrass, glyphosate reduced above-ground biomass by 96, 99, 94, and 62%, respectively compared with the untreated control (Table 2). Soltani et al (2013) reported that glyphosate applied to corn at the eight-leaf stage caused similar levels of biomass reductions for velvetleaf, redroot pigweed, common ragweed, and common lambsquarters 6 WAT and rated the control of these species at this timing as 100%.…”
Section: Weed Biomassmentioning
confidence: 95%
See 1 more Smart Citation
“…However, in Environ2, corn yield was not impacted by glyphosate dose or timing. In the literature, reference [7] reported no injury or subsequent yield loss when corn was treated at the 10-leaf stage with 900 g•ae•ha −1 of glyphosate. However, in Ontario, a single application of glyphosate at or after the 8-leaf stage risks yield loss due to early-season competition with weeds [15] and is not recommended [9].…”
Section: Late Application Experimentsmentioning
confidence: 99%
“…Currently, glyphosate-resistant hybrids have become adopted widely in North America since their introduction. For example, over 90% of hectares planted in Eastern Canada, the predominant Canadian corn growing region, are glyphosate-resistant hybrids [7]. In the USA, herbicide-resistant corn, glyphosate resistance the predominant weed management trait, accounted for 85% of corn acreage by 2013 [8].…”
Section: Introductionmentioning
confidence: 99%